234k views
4 votes
80 points!!! I desperately need help! tell me how to do this! PLZ
(4k+5)(k+1)=0

User Baldewin
by
5.7k points

2 Answers

5 votes

Lets solve your equation step by step:

(4k + 5)(k + 1) = 0



Step 1: Simplify both sides of the equation:

4k^2 + 9k + 5 = 0



Step 2: Factor left side of equation:

(4k + 5)(k + 1) = 0



Step 3: Set factors equal to 0:


4k + 5 = 0 or k + 1 = 0


k = - 5/4 or k = - 1






Answer: k = - 5/4 or k = - 1








Hope that helps!!!! ( Answer: k = -5/4 or k = -1)

User Soham Lawar
by
6.3k points
6 votes

Use distributive property to get 4k^2 +9k+5 and factor it from there. You should get (4k+5)(4k+4).

User Yane
by
5.5k points